A simple and safe antibody neutralization assay based on polio pseudoviruses - Zheng Jiang; Guixiu Liu; Liao Guo-yang; Mingbo Sun; Kangwei Xu; Zhifang Ying; Jianfeng Wang; Xuguang Li; Changgui Li (Taylor & Francis Group, 2019)
The evaluation of the immunogenicity of Sabin strain based Inactivated Poliovirus Vaccines (sIPV) necessitates the use of wild strains in neutralization assays to assess the potential cross-reactivity of antibodies. The live virus strains including wild and Sabin strains must be handled in level 3 biocontainment laboratories. To develop an alternative assay without the use of a live virus, we constructed Mahoney, MEF-1, and Saukett pseudovirions by inserting luciferase reporter genes into intact capsid proteins. Afterward, we developed a pseudovirus-based neutralization test (pNT) and evaluated for the specificity and reproducibility. We tested serum samples from a clinical trial on sIPV vaccines by pNT and compared the results with those obtained from conventional neutralization tests (cNT). A strong correlation was observed between two methods, with the correlation coefficients of all three types of IPV vaccines being greater than 0.82 (p < 0.0001). The Geometric Mean Titer (GMT) values obtained by pNT were approximately four times higher than that by cNT, revealing the better sensitivity of pNT. In conclusion, pNT is a safe, rapid and sensitive quantitative assay with the potential of being an alternative for the evaluation of the potency of polio vaccines.